X-ray spectra of Sagittarius A East and diffuse X-ray background near the Galactic center. (9th April 2019) - Ono, Akiko; Uchiyama, Hideki; Yamauchi, Shigeo; Nobukawa, Masayoshi; Nobukawa, Kumiko K; Koyama, Katsuji
Abstract: This paper reports the analysis procedure and results of simultaneous spectral fits of the Suzaku archive data for Sagittarius (Sgr) A East and the nearby Galactic center X-ray emission (GCXE). The results are that the mixed-morphology supernova remnant Sgr A East has a recombining plasma (RP) with Cr and Mn Heα lines, and a power-law component (PL) with an Fe i Kα line. The nearby GCXE has a ∼1.5-times larger surface brightness than the mean GCXE far from Sgr A East, although the spectral shape is almost identical. Based on these results, we interpret that the origins of the RP and the PL with the Fe i Kα line are past big flares of Sgr A ⋆ .